Food insecurity and the social division of labour in Tanzania, 1919-1985 - Bryceson, D; Bryceson, Deborah Fahy (1988)
﻿ This thesis analyzes the socio-economic consequences of the Tanzania population's exposure to food insecurity between 1919 and 1985. The thesis covers: the incidence of food inadequacy in peasant households throughout the country; the impact of famine relief measures of the colonial state and the Native Authorities; the role of Asian traders; the development of an African wage labour force and its food demand; the problems of supplying food to plantation workers and other geographically dispersed wage labourers during the inter-war period; state food policies arising from the exigencies of World Mar II; decolonisation and the restructuring of the social division of labour on a non-racial basis between 1950 and 1973; state food production and Marketing policy in response to rapid urban growth; African marketing cooperatives, the national economic crisis years between 1973 and 1985; the parastatalisation of national marketed food supply; the parallel food market; the state's difficulties in implementing its industrialisation and peasant agricultural transformation policies; and the deterioration of the functional division of labour to the extent that the occupational division of labour between rural and urban areas blurs. The central argument of the thesis is that food insecurity retards development of functional social groups and the organisational structure of the market and state relative to the household and clientage networks. This situation arises from the prevalence of risk-averting, household-based strategies of all functional groups in contradistinction to the maximizing strategies of market and state agents. With domination of household and clientage networks, the formation of functional groups is restricted to that made possible by face-to-face accountability or household ties. A circular process begins. Food insecurity is perpetuated and often intensified by the limited scale of the division of labour, its barriers to outside innovation and to the free flow of food between deficit and surplus areas through market channels. In the process, the technological development of food production is severely hindered.